Evaluating the effects of two different kinesiology taping techniques on shoulder pain and function in patients with hypermobile Ehlers-Danlos syndrome - Tudini, Frank; Levine, David; Healy, Michael; Jordon, Max; Chui, Kevin (Frontiers in Pain Research, 2023)
Background Ehlers-Danlos Syndrome (EDS) is a group of inherited connective tissue disorders which predominantly affects women and has a prevalence as high as 1 in 5,000 individuals. Hypermobile EDS (hEDS) is the most common subtype of EDS and is characterized by multi-joint pain, particularly in large joints such as the shoulder. Physical therapy is often utilized to address the pain, physical impairments, and functional loss in patients with EDS. Kinesiology Tape (KT) is an intervention commonly used by physical therapists for treating shoulder pain and dysfunction. Studies related to the effectiveness of KT in patients with shoulder pain is equivocal and there are a lack of studies specifically studying the effects of KT in an EDS population. Purpose The purpose of this study was to assess the efficacy and short-term effects of two different KT techniques on shoulder pain and function in individuals with hEDS and shoulder pain. Methods Participants were recruited from EDS support groups in the New England area of the United States; were diagnosed with hEDS by their physician; and had shoulder pain. Baseline demographic information was obtained for each participant followed by completion of 4 patient reported outcome (PRO) measures: the Upper Extremity Functional Index, QuickDASH (Disabilities of the Arm, Shoulder, & Hand), Shoulder Pain and Disability Index, and the Western Ontario Shoulder Instability Index. Current pain level, average pain over the past 24 h, and worst pain over the past 24 h were recorded using the numeric pain rating scale (NPRS). Subjects were randomly assigned to receive either an experimental shoulder KT procedure or a control shoulder taping. Immediately after taping, the NPRS was reassessed. Subjects then returned 48 h later to repeat the NPRS and PRO measures. Results There was no significant difference between the experimental and control tape groups for any outcome measure. There was a significant improvement from pre-taping to 48-hours post taping for each of the 4 PRO measures with large effect sizes (p < 0.001; ƞp2 = .517–.719). Likewise, average, and worst pain over the last 24 h significantly improved with large effect sizes over the same period (p = 0.005; ƞp2 = .225 and p < 0.001; ƞp2 = .382, respectively). Current NPRS levels significantly improved from pre-tape to immediately post-tape (p = .023, ƞp2 = .131) and was maintained through the 48-hour follow up, although no further improvement was seen. Conclusion KT is an inexpensive and relatively safe intervention that is easy to apply and can offer temporary improvements in pain and function for patients with EDS and shoulder pain.